The Apple experience : [electronic resource] : secrets to building insanely great customer loyalty - Gallo, Carmine (McGraw-Hill, 2012)
Reveals the secrets to the pioneering brand's unparalleled success during one of the most difficult retail environments in decades. In this title, the author uncovers the five steps of service that the company's customer-facing employees follow in Apple Stores to engage customers